Control System for Swerve Drive Wheeled Automated Guided Vehicle with Ultra-Wide Band Local Positioning System - Arifianto, Mada Jimmy Fonda; Afianto; Suhendra (Indonesian Journal of Engineering Research, 2023)
Control system for Automates Guided Vehicle (AGV) is used to control the motor movement so that the AGV can go to a position in certain speed and orientation. Discussion in this paper is about how to control 4-wheel swerve drive-based AGV. Mechanical structure of each wheel is built in such a way that the wheel can move forward / backward and the orientation can be adjusted while moving. Each wheel requires two BLDC motors to drive and to steer the AGV. In this project, the power each motor is 200W which is drove and controlled by Syntron LS20530G motor driver that connected to a computer via CAN-bus. An Ultra-Wide Band (UWB)-based Local Positioning System (LPS) is used to monitor the position of the AGV as well as a guide for non-physical paths so that AGV moves according to a given path virtually. The experimental results show that AGV can move in a straight line with a speed of 50m/min. Wheels can also be steered according to a certain angle so that the AGV can move towards the destination point. The steering angle of each wheel is between -135 degrees to 135 degrees.